Adaptive synchronization of quaternion-valued neural networks with reaction–diffusion and fractional order - Zhang, Weiwei; Zhao, Hongyong; Sha, Chunlin (Nonlinear Analysis: Modelling and Control, 2024)
This paper is dedicated to the study of adaptive finite-time synchronization (FTS) for generalized delayed fractional-order reaction–diffusion quaternion-valued neural networks (GDFORDQVNN). Utilizing the suitable Lyapunov functional, Green’s formula, and inequalities skills, testable algebraic criteria for ensuring the FTS of GDFORDQVNN are established on the basis of two adaptive controllers. Moreover, the numerical examples validate that the obtained results are feasible. Furthermore, they are also verified in image encryption as the application.
Keywords: adaptive synchronization; reaction–diffusion; finite time; quaternion-valued neural networks; image encryption